2013
DOI: 10.1039/c2sc21673f
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects on palladium-catalyzed deprotonative-cross-coupling processes (DCCP) of sp3C–H bonds in diarylmethanes

Abstract: Palladium-catalyzed cross-coupling reactions have become one of the most useful tools in modern organic chemistry. Current methods to achieve direct functionalization of sp 3 C-H bonds of arenes and heteroarenes often employ substrates with appropriately placed directing groups to enable reactivity.Examples of intermolecular arylation methods of weakly acidic sp 3 C-H bonds in the absence of directing groups, however, are still limited. We describe herein a study on the use of additives in Pd-catalyzed deproto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 99 publications
0
59
0
1
Order By: Relevance
“…[11] Following this line of reasoning, we tested the more reactive bases NaN(SiMe 3 ) 2 and KN(SiMe 3 ) 2 . [4] At rt in THF, we observed trace formation of products after 0.5 h with both NaN(SiMe 3 ) 2 and KN(SiMe 3 ) 2 . Heating reaction mixtures with NaN(SiMe 3 ) 2 or KN(SiMe 3 ) 2 to 50°C for 1 h resulted in coupled product 6a in 84% yield for the benzyl cyclohexyl sulfide with NaN(SiMe 3 ) 2 (entry 1, Table 6).…”
Section: Resultsmentioning
confidence: 96%
“…[11] Following this line of reasoning, we tested the more reactive bases NaN(SiMe 3 ) 2 and KN(SiMe 3 ) 2 . [4] At rt in THF, we observed trace formation of products after 0.5 h with both NaN(SiMe 3 ) 2 and KN(SiMe 3 ) 2 . Heating reaction mixtures with NaN(SiMe 3 ) 2 or KN(SiMe 3 ) 2 to 50°C for 1 h resulted in coupled product 6a in 84% yield for the benzyl cyclohexyl sulfide with NaN(SiMe 3 ) 2 (entry 1, Table 6).…”
Section: Resultsmentioning
confidence: 96%
“…We have found that trapping the resulting anion by benzylation allows us to determine which bases are capable of deprotonation of the substrates and serves as a starting point for optimization of the deprotonation step. 12 The reaction between benzophenone imine 1a and benzyl chloride (Scheme 3) was examined in the presence of 12 bases [LiN(SiMe 3 ) 2 , NaN(-SiMe 3 ) 2 , KN(SiMe 3 ) 2 , LiO– t Bu, NaO– t Bu, KO– t Bu, NaH, LiOAc, KOAc, K 3 PO 4 , Cs 2 CO 3 , and KOPh, see ESI for details † ]. Reactions were conducted in THF and CPME (cyclopentyl methyl ether) on microscale (10 μmol) at rt for 12 h. NaN(SiMe 3 ) 2 , KN(SiMe 3 ) 2 and KO- t Bu generated the benzylated product.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that different phosphine ligands are required (Figure 1, ligands L1–L5 ) for the diverse substrate classes and bases we have employed. This method has proven successful for the direct C–H arylation of diarylmethanes ( L1 ), [19] benzylic ketimines ( L1 ), [20] benzyl thioethers, [21] benzylic phosphine oxides ( L2 ), [22] methyl sulfoxides and sulfones ( L3 ), [23] amides ( L3 ), [24] benzylic phosphonates ( L4 ), [25] and allyl benzenes ( L5 ). [26] …”
Section: Resultsmentioning
confidence: 99%